Excellent photoluminescence and temperature sensing properties in Ho3+/Yb3+ codoped (Y0.88La0.09Zr0.03)2O3 transparent ceramics. Issue 6 (15th April 2019) - Zhou, Jun; Chen, Yaqian; Lei, Ruoshan; Wang, Huanping; Zhu, Qingong; Wang, Xingming; Wu, Yuqian; Yang, Qinghua; Xu, Shiqing
Abstract: Ho 3+ /Yb 3+ codoped (Y0.88 La0.09 Zr0.03 )2 O3 transparent ceramics were prepared by a high temperature solid-state reaction method. SEM observation confirms that there are no obvious impurities or pores existed in the grain boundaries of the samples. Accordingly, all the samples show excellent transparency in the visible and near-infrared range. Upon 980 nm excitation, strong green emission peaked at 549 nm, red emissions centered at 667 and 756 nm, as well as near infrared emission located at 2 µm respectively from Ho 3+ ions are observed. By utilizing the fluorescence intensity ratio (FIR) technique, the temperature sensing behaviors of the optimal sample (Yb0.03 Ho0.01 Y0.84 La0.09 Zr0.03 )2 O3 are investigated at different excitation power densities based on the non-thermally coupled levels of 5 F4 / 5 S2 and 5 F5 . The thermometry is found to be immune to the excitation power density, leading to the consistent calibration curves and sensing sensitivities at the different power densities. The maximal sensing sensitivity is about 71.28 × 10 −4 K −1 at 563 K. The results indicate that the Ho 3+ /Yb 3+ codoped (Y0.88 La0.09 Zr0.03 )2 O3 transparent ceramics are promising for the temperature sensors, display devices and 2 µm solid-state lasers.